Coping with Crises : Why and How to Protect Employment and Earnings - Virjee, K.; Gaskin, S. (2012)
Trinidad and Tobago's 1.3 million residents are provided water supply and sewerage services by a national utility whose service levels have been inadequate and deteriorating through the recent past, largely due to a lack of investment in utility infrastructure. A owillingness to payo study assessed the degree of coverage and quality of service and the residents' willingness to accept water tariff increases for an increase in service level. Willingness to pay for change is low, below current tariffs, due to scepticism about the likelihood of change and due to the ability to cope with bad service through the pervasive use of local storage.